Determination of the amount of wet corn gluten feed to include in diets for lactating dairy cows - VanBaale, M. J.; Scheffel, Michael V.; Titgemeyer, Evan C.; Lindquist, R.U.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twenty-four multiparous Holstein cows were used in six 4×4 Latin squares with 28- day periods to determine inclusion rates for wet corn gluten feed (WCGF) in diets for lactating dairy cows. Cows were housed in a tie-stall barn and fed diets to meet or exceed NRC (1989) nutrient requirements. Experimental treatments were 1) control, 2) WCGF constituting 20%, 3) WCGF constituting 27.5%, and 4) WCGF constituting 35% of the diet dry matter. Cows fed WCGF consumed more dry matter (P<0.01) and produced more (P<0.001) milk, energy-corrected milk, and fat-corrected milk than cows fed the control diet. Dry matter intakes were 58.9 lb/day for control and 60.2 lb/day for those cows consuming WCGF diets. Cows fed the control diet produced 83.2 lb/day of milk, whereas those fed WCGF diets produced 91.5 lb/day. Production efficiency was increased (P<0.001) on the WCGF diets. The percentage of fat in milk, total protein production, and milk urea nitrogen were higher (P<0.01) for cows fed WCGF diets than controls. Plasma glucose, total alphaamino nitrogen, urea nitrogen, and tryglycerides were similar between cows fed the control and WCGF diets. No differences occurred in percentages of protein, lactose, or solids-not-fat content, nor was somatic cell count affected by the addition of WCGF. Body weight and condition score were not affected by treatment. We conclude that WCGF is an excellent feed for lactating dairy cows when included in the diet at 20%, 27.5%, or 35% of the dry matter.
Keywords: Dairy; Wet corn gluten; Lactating cows; Milk; Milk yield